CuO/ZnO/TiO2 photocathodes for a self-sustaining photocell: Efficient solar energy conversion without external bias and under visible light. (28th February 2020) - Shaislamov, Ulugbek; Kim, Hyun; Yang, Jun Mo; Yang, Bee Lyong
Abstract: We report the results of a p -CuO nanoflake photocathode combined with an n-type TiO2 nanorod-based photoanode in a solar-water-splitting photocell, operating without external bias under visible light illumination. Both p -CuO nanoflakes and n-TiO2 nanorods were successfully fabricated by a low-cost solution-based method on transparent conductive substrates. Photocorrosion of the CuO electrode was suppressed by coating with a 200-nm ZnO/TiO2 protective film, which demonstrated a stability of over 70%. The visible-light response of single crystalline n-TiO2 nanorods was enhanced by sensitization with CdS/CdSe nanoparticles. Finally, the two n- and p-type photoelectrodes were short-circuited in the photocell, and their current-voltage (I–V) characteristics evaluated under visible-light illumination. The results of the I–V measurements reveal that the performance of the photocell strongly depends on the electrochemical properties of each electrode. The photocell comprising highly stable p -CuO and visible-light-active n-TiO2 -based photoelectrodes operating without external bias demonstrated a short-circuit current and photoconversion efficiency of ~1 mA and 0.57%, respectively, under visible-light illumination. Graphical abstract: Image 1 Highlights: Double electrode cell was proposed for unassisted H2 generation by water splitting. Photocorrosion of the CuO was addressed by coating with a ZnO/TiO2 protective layer. p -CuO/ZnO/TiO2 and n-TiO2 /CdS/CdSe photoelectrodes forms suitable band alignment. Built in potential in p -CuO/ZnO/TiO2 electrode contributes to the charge separation.